Improving Aqueous Solubility of Natural Antioxidant Mangiferin through Glycosylation by Maltogenic Amylase from Parageobacillus galactosidasius DSM 18751 - Jiumn-Yih Wu; Hsiou-Yu Ding; Tzi-Yuan Wang; Yu-Li Tsai; Huei-Ju Ting; Te-Sheng Chang (MDPI AG, 2021)
Mangiferin is a natural antioxidant C-glucosidic xanthone originally isolated from the Mangifera indica (mango) plant. Mangiferin exhibits a wide range of pharmaceutical activities. However, mangiferin's poor solubility limits its applications. To resolve this limitation of mangiferin, enzymatic glycosylation of mangiferin to produce more soluble mangiferin glucosides was evaluated. Herein, the recombinant maltogenic amylase (MA; E.C. 3.2.1.133) from a thermophile Parageobacillus galactosidasius DSM 18751T (PgMA) was cloned into Escherichia coli BL21 (DE3) via the expression plasmid pET-Duet-1. The recombinant PgMA was purified via Ni2+ affinity chromatography. To evaluate its transglycosylation activity, 17 molecules, including mangiferin (as sugar acceptors), belonging to triterpenoids, saponins, flavonoids, and polyphenol glycosides, were assayed with β-CD (as the sugar donor). The results showed that puerarin and mangiferin are suitable sugar acceptors in the transglycosylation reaction. The glycosylation products from mangiferin by PgMA were isolated using preparative high-performance liquid chromatography. Their chemical structures were glucosyl-α-(1→6)-mangiferin and maltosyl-α-(1→6)-mangiferin, determined by mass and nucleic magnetic resonance spectral analysis. The newly identified maltosyl-α-(1→6)-mangiferin showed 5500-fold higher aqueous solubility than that of mangiferin, and both mangiferin glucosides exhibited similar 1,1-diphenyl-2-picrylhydrazyl free radical scavenging activities compared to mangiferin. PgMA is the first MA with glycosylation activity toward mangiferin, meaning mangiferin glucosides have potential future applications.